Prolonged resuscitation and systemic management of multi-organ dysfunction in a neonate with severe asphyxia: a case report - Wang, Qingsong; Yin, Jun; Wang, Junru; Zhao, Zhihui; Du, Taojun; Ou, Huimin; Cao, Hongmei; Zhang, Hong; Cao, Haonan; Yue, Wenlong; Jiang, Siguang; Luo, Tongyong; et al. (Frontiers in Pediatrics, 2025)
Severe neonatal asphyxia can lead to multiple organ dysfunction syndrome (MODS) and increase mortality and disability risks. This case report describes the successful resuscitation and management of a neonate who experienced 15 min of severe asphyxia. The male infant, born at 36 weeks’ gestation via emergency cesarean section, had extremely low Apgar scores (1 at 1, 5, and 10 min). He underwent 15 min of resuscitation, including airway clearance, endotracheal intubation, positive pressure ventilation, chest compressions, and multiple administrations of epinephrine. Post-resuscitation, he exhibited severe dysfunction in multiple organ systems. The infant received comprehensive treatment, including invasive mechanical ventilation, continuous renal replacement therapy (CRRT) for acute kidney injury, therapeutic hypothermia for neuroprotection, surgical treatment for necrotizing enterocolitis with perforation, and specialized nutritional support. His condition significantly improved, with resolution of MODS, and he was discharged with weight gain and good feeding tolerance. Neurological assessments at discharge showed no significant abnormalities; however, long-term follow-up is ongoing to monitor for potential neurodevelopmental outcomes. This case highlights the importance of timely resuscitation and meticulous systemic management in achieving a favorable prognosis for neonates with severe asphyxia and MODS. The successful collaboration of a multidisciplinary team played a key role in the neonate's recovery.